2019
DOI: 10.1007/s42995-019-00002-5
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the diagnosis of bacterial fish diseases

Abstract: The diagnosis of bacterial fish diseases has progressed from traditional culture-dependent methods involving the recovery of pathogens on agar-containing media and identification by examination of phenotypic traits. Newer approaches centre on culture-independent approaches. A problem with culturing is that it lacks sensitivity, tends to be slow, and its success depends on the composition of the media and incubation conditions employed. In contrast, culture-independent methods, now centring on molecular methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Signs of septicemia observed on infected fish were associated with expressing the different virulence factors of the invading bacterial pathogens. In harmony with the present results; Austin (2019) reported that signs of septicemia are the most prominent indicator of bacterial fish diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Signs of septicemia observed on infected fish were associated with expressing the different virulence factors of the invading bacterial pathogens. In harmony with the present results; Austin (2019) reported that signs of septicemia are the most prominent indicator of bacterial fish diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst previous research has also demonstrated the importance of sample location in isolation of particular compartment-specific subsets of GIT microbial communities [ 49 , 50 ], there exists no published data regarding the impact of sampling methodology or localisation on gill communities. Traditional microbiological culture techniques obtain microbiota from tissue sections directly, or by swabbing the gill surface [ 51 ], and remain important in pathogen diagnosis. Many marine microbiota are considered particularly difficult to culture however, and sequencing is often more successful in isolation of diverse communities.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of bacterial pathogens, both from fish and other sources, has increasingly been based on the use of polymerase chain reaction (PCR) based approaches over the past two decades 21 . One significant drawback of this approach is that it can only be used to test for known pathogens, with multiple presence/absence tests needed to check for all potential pathogens.…”
Section: Introductionmentioning
confidence: 99%